Flying triangulation - A motion-robust optical 3D sensor for the real-time shape acquisition of complex objects - Häusler, Gerd; Ettl, Svenja; Arold, Oliver; Yang, Zheng (Applied Optics, 2012)
Three-dimensional (3D) shape acquisition is difficult if an all-around measurement of an object is desired or if a relative motion between object and sensor is unavoidable. An optical sensor principle is presented-we call it "flying triangulation"-that enables a motion-robust acquisition of 3D surface topography. It combines a simple handheld sensor with sophisticated registration algorithms. An easy acquisition of complex objects is possible-just by freely hand-guiding the sensor around the object. Real-time feedback of the sequential measurement results enables a comfortable handling for the user. No tracking is necessary. In contrast to most other eligible sensors, the presented sensor generates 3D data from each single camera image.
Keywords: optical 3D metrology; motion robust; triangulation

Joint Surface Reconstruction and 4D Deformation Estimation from Sparse Data and Prior Knowledge for Marker-Less Respiratory Motion Tracking - Berkels, Benjamin; Bauer, Sebastian; Ettl, Svenja; Arold, Oliver; Hornegger, Joachim; Rumpf, Martin (Medical Physics, 2013)

Marker-less reconstruction of dense 4-D surface motion fields using active laser triangulation for respiratory motion management - Bauer, Sebastian; Berkels, Benjamin; Ettl, Svenja; Arold, Oliver; Hornegger, Joachim; Rumpf, Martin (15th International Conference, Nice, France, October 1-5, 2012, Proceedings, Part I, 2012)
To manage respiratory motion in image-guided interventions a novel sparse-to-dense registration approach is presented. We apply an emerging laser-based active triangulation (AT) sensor that delivers sparse but highly accurate 3-D measurements in real-time. These sparse position measurements are registered with a dense reference surface extracted from planning data. Thereby a dense displacement field is reconstructed which describes the 4-D deformation of the complete patient body surface and recovers a multi-dimensional respiratory signal for application in respiratory motion management. The method is validated on real data from an AT prototype and synthetic data sampled from dense surface scans acquired with a structured light scanner. In a study on 16 subjects, the proposed algorithm achieved a mean reconstruction accuracy of +/- 0.22 mm w.r.t. ground truth data.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD5.marker

Optimierte Segmentierung der Papille in HRT-Retinaaufnahmen - Arold, Oliver; Bock, Rüdiger; Meier, Jörg; Michelson, Georg; Hornegger, Joachim (Bildverarbeitung für die Medizin 2008 - Algorithmen, Systeme, Anwendungen, 2008)